Histopathological and biochemical effect of Liv-52 on rifampicin and isoniazid induced liver toxicity in adult albino rats - Libamila, Hans Lwunza (International Journal of Research in Medical Sciences, 2024)
Background: Rifampicin and Isoniazid are two main medicinal drugs used as regimen in the treatment of Tuberculosis. These drugs induce hepatotoxicity. Liv-52, a polyherbal formulation has been shown to have clinical use in the treatment of liver disorders. The aim of this study was to investigate the histopathological and biochemical effects of Liv-52 on INH and RIF induced hepatotoxicity. Methods: Adult albino rats weighing 150g to 250g were used. A total of 24 rats were randomly assigned into 4 groups of 6 rats each. Group 1 served as negative control. Hepatotoxicity was achieved by administering 50 mg/kg/day of RIF and INH each as positive control. Hepatoprotective effect was determined by administering Liv-52 concurrently with positive control. Low dose Liv-52 and high dose Liv-52 was administered at (155 mg/kg/day and 207 mg/kg/day) respectively, concurrently with RIF and INH at (50 mg/kg) each orally daily. After 21 days, the albino rats were sacrificed humanely, liver harvested and blood samples taken for estimation of liver serum biomarkers. The livers were processed and stained with Haematoxylin and Eosin for histological examination. Significance levels of (p≤0.05). Results: The three selected liver biochemical parameters (ALT, AST and ALP) significantly increased in positive control group relative to negative control. The hepatoprotective groups (especially the HD Liv-52 group) showed significant reduction in the biochemical parameters. The liver histopathological results confirmed the above findings. Conclusion: High dose Liv-52 significantly prevents hepatotoxicity induced by antitubercular therapy by inhibiting rise liver biochemical parameters and also ameliorating the deranged liver histomorphological features.